PENGARUH BEBAN KERJA DAN KOMUNIKASI TERHADAP SEMANGAT KERJA PEGAWAI SAMSAT PANDA BIMA - Dewi Sekar Wangi; Firmansyah Kusumayadi (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
This type of research is associative with a quantitative approach. The population in this study was 33 Samsat Panda office employees. The sampling technique used in this research was saturated sampling so the number of samples in this research was 33 respondents. Data was processed using SPSS 23.0. From the results of the multiple linear regression test, there is a relationship between workload and communication on work morale. The results of this research indicate that the Workload variable (X1) has a partially significant effect on the Work Morale of the Samsat Panda Office employees. The Communication variable (X2) has a partially significant effect on the work morale of the Samsat Panda Office employees. The variables Workload and Communication simultaneously have a significant effect on Work Morale among Panda Bima Samsat Employees.